Kecerdasan Spritual dan Lingkungan Keluarga Mempengaruhi Hasil Belajar IPS Ekonomi - Helena Rosalia Parera (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
This study aims to determine the effect of spiritual intelligence and family environment on social studies learning outcomes. This type of research is quantitative research. The research method is Ex-Post Facto using an associative approach, data analysis using multiple regression analysis. The results of the data were measured using a closed questionnaire.minimum score per item is one then the max score per item is four.The ideal score range is 15 to 60. The results show that: Spiritual intelligence and family environment are in the high categoryThere means that these two variables, spiritual intelligence, family environment, have a hight influence on learning outcomes in Economic Social Studies. Them learning outcomes of students themselves fall into the low category due to the low ability of students to remember the past material that has been past students do not work on the problem. Overall spiritual intelligence, the family environment affects the learning outcomes of students in the Social Studies subject.